Evaluation of the Clinical Outcomes of Breast Cancer Patients with Positive and Negative Circulating Tumor DNA: A Meta-analysis and Systematic Review - Maryam Fathi; Seyedeh Solmaz Riazi; Zahra Ghaziani; Fatemeh Hodaie (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2024)
Background and aim: This research addressed predicting the risk levels of breast cancer recurrence through the Circulating Tumor DNA (ctDNA) diagnostic method. The primary objective of the research was the evaluation of the clinical outcomes of cases suffering from breast cancer who exhibited positive and negative ctDNA.Material and methods: To achieve the objectives of the study, databases at the international scale, including Web of Science, PubMed, Science Direct, Wiley, Scopus, EBSCO, Web of Knowledge, ISI, Embase, Google Scholar, and Elsevier, were searched according to PRISMA 2020-27-item checklist and respective keywords from 2019 to February 2024. Moreover, the inverse-variance method and the fixed effect model were applied to the research. In addition, we used STATA/MP v17 for statistical analyses of the data (Sig, ˂ 0.05).Results: Based on the search, 11 articles were chosen, considering the inclusion criteria intended for the research. The odds ratio (OR) of ctDNA measurements with the positive result equaled 47% with a significant p-value compared to the negative ctDNA. Thus, similar overall survival was found in three (3) time points (P = 0.83). Furthermore, the detection rate of the positive versus negative ctDNA was found to be 72% (ES:72% 95% CI; 54%-89%) in the baseline and 44% (ES:44% 95% CI; 12%-100%) during neoadjuvant chemotherapy. Consequently, the negative conversion rate of the positive versus the negative ctDNA in the baseline-during neoadjuvant chemotherapy equaled 52% (ES:0.52 95% CI; -0.30-1.33), but it was 60% during neoadjuvant chemotherapy before the surgical operation (ES:0.60 95% CI; -0.71-1.91). Given testing the group differences, we did not observe any significant differences between the mentioned time points.Conclusions: The performed meta-analysis revealed the potential of ctDNA to be applied as one of the reference indexes for evaluating the treatment effects during NAT, before and after surgical operation, and at baseline.